2000
DOI: 10.1002/1521-4141(200006)30:6<1538::aid-immu1538>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ regulatory T cells down-regulate co-stimulatory molecules on antigen-presenting cells

Abstract: CD4+CD25+ T cells have been shown to inhibit experimentally induced organ‐specific autoimmune disease and depletion of these regulatory T cells from normal mice results in development of such conditions. Furthermore, CD4+CD25+ T cells suppress the IL‐2 production and thereby the proliferation of polyclonally activated CD4+CD25– T cells in vitro. The suppression in vitro is independent of secreted factors but requires interactions between CD4+CD25– and CD4+CD25+ T cells and antigen‐presenting cells (APC). We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
266
3
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(291 citation statements)
references
References 9 publications
11
266
3
8
Order By: Relevance
“…This idea is reinforced by the observation that in vitro suppression was abrogated in the presence of APCP, a CD73-specific inhibitor (data not shown). Another well-known suppressive function of Treg cells includes the control of DC maturation and activation by CTLA-4 and LAG-3 expression [62][63][64][65][66]. The high expression of these molecules by RA-iTreg cells supports the notion that these cells may regulate the immune response by also suppressing DC function.…”
Section: Discussionmentioning
confidence: 81%
“…This idea is reinforced by the observation that in vitro suppression was abrogated in the presence of APCP, a CD73-specific inhibitor (data not shown). Another well-known suppressive function of Treg cells includes the control of DC maturation and activation by CTLA-4 and LAG-3 expression [62][63][64][65][66]. The high expression of these molecules by RA-iTreg cells supports the notion that these cells may regulate the immune response by also suppressing DC function.…”
Section: Discussionmentioning
confidence: 81%
“…The Tol-DC subset possesses low levels of MHC class II, CD80/86, and IL-12, while secreting high levels of 20). In contrast, T cells that secrete TGF-␤ and IL-10 also can promote the generation of Tol-DC with immature phenotype (21,22). However, these studies are in vitro, and demonstrate a oneway regulation of Treg on Tol-DC and Tol-DC on Treg, respectively.…”
Section: Inhibitory Feedback Loop Between Tolerogenic Dendritic Cellsmentioning
confidence: 92%
“…It has been reported that CD4 ϩ CD25 ϩ cells can be generated in vitro by activation of naive T cells in the presence of immature DC that possess low levels of MHC class II, CD80/86, and IL-12, but secrete high levels of IL-10 (10, 20). In contrast, anergized T cells secreting TGF-␤ and IL-10 also can promote the generation of Tol-DC with immature phenotype (21,22). However, the mutual relationship between Tol-DC and Treg has never been investigated in transplant tolerance.…”
Section: Inhibitory Feedback Loop Between Tol-dc and Treg In Transplamentioning
confidence: 99%
“…In this context, it was demonstrated that DC cultured in the presence of IL-10 suppress the response of Ag-specific naive or activated CD4 + T cells and promote the generation of T regulatory cells [41,42]. CD4 + CD25 + regulatory T cells down-regulate costimulatory molecules on APC even in the presence of stimuli that would normally increase their expression [43]. Helminthinduced T regulatory cells play also an important role in the general state of immunosuppression observed in some infections [8][9][10].…”
Section: Discussionmentioning
confidence: 99%